Aniceto Rapozo’s cabinet at the Lisbon Academy of Sciences - Saporiti Machado, J. (2014)
From the end of the eighteenth until the beginning of the nineteenth century, wood samples were regularly sent to the Royal Army Arsenal in Lisbon for testing. The large number and variety of samples, as well as increasing interest on Brazil, explain why, in 1805, the Prince Regent of Portugal commissioned the preparation of four collections containing 1,213 timber specimens from Brazil and twelve from other origins. One of these collections, housed in a cabinet at the Lisbon Academy of Sciences, is now being studied in order to reveal its origins and to identify the wood samples. Botanical identifications will provide valuable information about the wood resources and the species used by furniture-makers in the late eighteenth and early nineteenth centuries.